KLASIFIKASI EMOSI TOKOH KINAN DALAM SERIAL DRAMA WEB SERIES “LAYANGAN PUTUS” PADA PERSPEKTIF PSIKOLOGI SASTRA - Niken Aprilyana; Abdillah Nugroho (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to determine the classification of emotions contained in the web series drama "Layangan Putus". The method used in this research is descriptive method, with the object that will be studied in this research is a web series drama "Layangan Putus" with director Benni Setiawan and screenwriter Oka Aurora. The data collection technique in this study was the note-taking technique. The results of the analysis of this web series drama, found seven classifications of emotions contained in the character Kinan. The emotional expressions that arise include: the emotion of happiness, the emotion of sadness, the emotion of fear, the emotion of hatred, the emotion of anger, the emotion of surprise, and the emotion of love. Expression of emotions usually arises spontaneously in each self and is spontaneous. Literary psychology is supported by three approaches including textual approach, acceptance-pragmatism approach, and expression approach. Keywords: emotion, expression, literary psychology